High rates of respiratory illnesses upon arrival: lessons from Team USA at the Santiago 2023 Pan American and Parapan American Games - Post, E. G.; Anderson, T.; Samson, O.; Triplett, A. N.; Gidley, A. D.; Isono, S. S.; Watters, J.; Donaldson, A. T.; Finnoff, J. T.; Adams, W. M. (British Journal of Sports Medicine, 2024)
Objective To describe the incidence and characteristics of injuries and illnesses among Team USA athletes competing at the Santiago 2023 Pan American Games (PAG) and Parapan American Games (PPAG), with a particular focus on the incidence of respiratory illnesses and on injuries for sports new to the Olympic and Paralympic programmes.